An Investigation of the Multilingual and Bi-dialectal Advantage in Executive Control - Antoniou, Kyriakos; Spanoudis, George (My University, 2020)
We examined the effect of speaking more than one language (multilingualism) or two dialects of the same language (bi-dialectalism) on executive control (EC) by administering seven EC tasks to 46 multilingual, 72 bi-dialectal and 47 monolingual young adults. We used the EC model of Miyake, Friedman, Emerson, Witzki, Howerter and Wager (2000) according to which EC comprises three components: working memory, task-switching and inhibition. We also tested two theoretical views regarding the locus of the bilingual advantage: first, that bilingualism affects specific EC components and, second, that bilingualism has a more general effect on the whole EC network. Miyake et al.'s (2000) model was a good fit to our EC data. We also found that both multilinguals and bi-dialectals had significantly higher EC scores than monolinguals. Moreover, both the multilingual and the bi-dialectal advantage was found in overall EC ability and could not be attributed to a specific EC component.
Keywords: bi-dialectalism; bilingualism; dialects; executive control; multilingualism; typological distance